[PP.22.12] EFFECTS OF OLMESARTAN MEDOXOMIL THERAPY ON ARTERIAL FUNCTION IN METABOLIC SYNDROME. (September 2017) - Ruiz, V.; Ferré, R.; Plana, N.; Ibarretxe, D.; Rodríguez, C.; Merino, J.; Masana, L.
Abstract : Objective: To explore endothelial function and arterial elasticity changes on metabolic syndrome patients treated with olmesartan medoxomil. Design and method: Thirty-two patients with metabolic syndrome with ACE inhibitors intolerance or naive for SRA inhibitors were assigned to receive olmesartan medoxomil 20 to 40 mg/daily plus thiazide, calcium antagonists or/and alpha-blocker when needed to reach optimum blood pressure control. cIMT, arterial stiffness (echotracking QIMT and QAS, Esaote), and endothelial function (EndoPAT, Itamar Medical) measures were performed before therapy and one-year later. Therapeutic lifestyle changes were also advised. 40-matched-age-and-gender-metbolic-syndrome controls were given ACE inhibitors and were equally observed. Results: Mean blood pressure was significantly reduced in both groups (- 24.8 2.6 mmHg, p < 0.001). cIMT showed no significant changes after one-year of treatment. Endothelial function improved, with a statistical significant change in olmesartan-treated group vs control group (dif 0.46 0.11, p = 0.02 on RHI) and also arterial elasticity (dif - 3.11 1.1 m/sec of PWV p < 0.001, dif –5.7 0.6% for AIx p = 0.002). Albumin/creatinine ratio was reduced in both olmesartan and control groups but 1-year differential was only statistically correlated with vascular function parameters in olmesartan-treated patients (r = - 0.45 for PWV and r = –0.37 for RHI). Multivariate analyses demonstrated a beneficial effect of olmesartan therapy for improving vascular function when compared with other SRA inhibitors. The main determinants for a better endothelial function and arterial elasticity were olmesartan treatment, physical activity increase and body weight loss. Conclusions: Treatment with olmesartan medoxomil in patients with metabolic syndrome showed an improvement on vascular elasticity and endothelial function in addition of lifestyle changes adherence or the effects of other antihypertensive therapy.